Diabetes and tumor risk: a 23-year Danish national cohort study - Skovbjerg, Katja F.; Antvorskov, Julie C.; Stokholm, Lonny M.; Bille, Tine D.; Andersen, Nis; Andresen, Jens; Bek, Toke; Hajar, Javad; Kawasaki, Ryo; Laugesen, Caroline S.; Möller, Sören; Pedersen, Frederik N.; et al. (Frontiers in Endocrinology, 2026)
IntroductionDiabetes mellitus is a recognized risk factor for cancer, yet the relationship between diabetes type and tumor risk remains unclear. This study aimed to estimate the overall tumor burden, including benign, premalignant, and malignant tumors, in individuals with type 1 and type 2 diabetes.MethodsIn this nationwide cohort study spanning 23 years (1999–2022), data on diabetes diagnosis, tumor development, and potential confounding variables were retrieved from multiple Danish national health registries. The cohort included more than 6.5 million individuals and 128,647 tumor events among individuals with diabetes. Crude and adjusted hazard ratios (HRs) were estimated using Cox regression. ResultsFor individuals with type 1 diabetes, adjusted HRs indicated no association for overall tumor development compared to individuals without diabetes. For individuals with type 2 diabetes, adjusted HRs suggested a slightly decreased hazard for overall tumor development compared to individuals without diabetes. When excluding tumors in the skin, the association between type 1 and type 2 diabetes and overall tumor development, suggested an increased hazard compared with individuals without diabetes. Our exploratory sub-analyses were stratified by tumor topography based on Systematized Nomenclature of Medicine (SNOMED) codes. Among individuals with type 1 diabetes, eight of 28 tumor groups showed reduced hazard, including the pancreas, bile ducts, and kidney. For type 2 diabetes, one group showed reduced hazard, while 22 groups, including the heart, blood vessels, and liver, showed increased hazard. Estimates from exploratory analyses should be interpreted with caution. DiscussionOur findings provide population-level evidence that advances our understanding of the possible complex metabolic links between diabetes and tumor development. Further exploration of SNOMED-based tumor classifications in future studies may provide valuable knowledge on pathological differences and refine future tumor and cancer surveillance strategies in individuals with diabetes.